2010
DOI: 10.1088/1742-6596/225/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

OH radical in water studied by Quantum beats on positron annihilation -the effect of water liquid structures-

Abstract: OH radical in water studied by Quantum beats on positron annihilation -the effect of water liquid structuresTo cite this article: Jeong-Jae Lee et al 2010 J. Phys.: Conf. Ser Abstract. Singlet radical pairs of ortho-positronium and hydroxyl (OH) radical were generated in positron radiolysis in water. Quantum beats on the energy distribution of positron annihilation γ-rays caused by the reaction of electron-spin-correlated pairs of orthopositronium and OH radical were newly measured at 32°C by using positron an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The diffusion is accompanied by multistep structural rearrangements of the OH radical in the 'water tube' (2.65 Å in length) of 11 (the first and second shells) water molecules. These rearrangements are the result of hydrogen bond forming/ breaking between the OH and water molecules; the O-H bond length in the radical varies in the intervalr max (O-H) = 1.12 Å, r min (O-H) = 0.96 Å-that coincides with the previously observed data [41]. When the OH is as close to the HO-C 2' as 1.54 Å, the H-O bond in the HO-C 2' displays a progressive lengthening.…”
Section: Posupporting
confidence: 89%
See 1 more Smart Citation
“…The diffusion is accompanied by multistep structural rearrangements of the OH radical in the 'water tube' (2.65 Å in length) of 11 (the first and second shells) water molecules. These rearrangements are the result of hydrogen bond forming/ breaking between the OH and water molecules; the O-H bond length in the radical varies in the intervalr max (O-H) = 1.12 Å, r min (O-H) = 0.96 Å-that coincides with the previously observed data [41]. When the OH is as close to the HO-C 2' as 1.54 Å, the H-O bond in the HO-C 2' displays a progressive lengthening.…”
Section: Posupporting
confidence: 89%
“…The reason for keeping the spins parallel on the both radicals is in the highly large HF constant , produced by the AMP -radical [25]. According to our computations (CPMD, section II), the value of  reaches 0.078 T. The strong magnetic coupling between the 31 P atom and the unpaired electron on the AMP -aligns the spin of OH (the  in the OH-(5H 2 O) complex at 310 K is 0.036 T-a result of the OH magnetic field enhancement by surrounding water molecules [41]) in the identical direction to that on the AMP -, and the environment cannot destroy the effect in the distance range 4.75 -1.50 Å between the AMP -and OH. The finding is crucial for the radical polymerization to occur, see below.…”
Section: Pomentioning
confidence: 75%
“…Lee et al indicated that the shape of S(t) changed with the elapsed time during measurements. [16] Even for 11°C, the shape changed during measurements. Now, the reason is not clear but change of the water liquid structures probably affected the shape of S(t).…”
mentioning
confidence: 98%